Colombia's cyberinfrastructure for biodiversity: Building data infrastructure in emerging countries to foster socioeconomic growth. Issue 3 (22nd December 2019) - De Vega, Jose J.; Davey, Robert P.; Duitama, Jorge; Escobar, Dairo; Cristancho‐Ardila, Marco A.; Etherington, Graham J.; Minotto, Alice; Arenas‐Suarez, Nelson E.; Pineda‐Cardenas, Juan D.; Correa‐Alvarez, Javier; Camargo Rodriguez, Anyela V.; Haerty, Wilfried; et al.
Societal Impact Statement: Colombia is a "megadiverse" country with vast natural resources. A history of recent conflict means that information is only now being collected on the natural capital of regions that were previously unexplored. Better access to data, tools, and expertise is required for evidence‐supported decisions on the conservation of these resources. The development of a bespoke cyberinfrastructure could help fulfill this need by providing access to digital resources in a collaborative cyberenvironment. We outline key priorities and develop a reference framework for building cyberinfrastructure in Colombia. This framework could be applied to other fields and countries to promote knowledge exchange, scientific innovation, and socioeconomic growth. Abstract : Colombia is a "megadiverse" country with vast natural resources. A history of recent conflict means that information is only now being collected on the natural capital of regions that were previously unexplored. Better access to data, tools, and expertise is required for evidence‐supported decisions on the conservation of these resources. The development of a bespoke cyberinfrastructure could help fulfill this need by providing access to digital resources in a collaborative cyberenvironment. We outline key priorities and develop a reference framework for building cyberinfrastructure in Colombia. This framework could be applied to other fields and countries to promote knowledge exchange, scientific innovation, and socioeconomic growth.